Osteointegration and Resorption of Intravertebral and Extravertebral Calcium Phosphate Cement. Issue 3 (April 2017) - Klein, Roman; Tetzlaff, Ralf; Weiss, Christel; Schäfer, Meike-Kristina; Tanner, Michael; Wiedenhöfer, Bernd; Grafe, Ingo; Meeder, Peter-Jürgen; Noeldge, Gerd; Nawroth, Peter P.; Kasperk, Christian
Abstract : Study Design: Eleven patients with painful osteoporotic vertebral fractures who underwent kyphoplasty using calcium phosphate (CaP) cement were followed up for 1 week, 1, 2, and 3 years in a monocentric, nonrandomized, noncontrolled retrospective trial. Objective: This study investigates long-term radiomorphologic features of intraosseous CaP cement implants and of extraosseous CaP cement leakages for up to 3 years after implantation by kyphoplasty. Summary of Background Data: Kyphoplasty is frequently used for the treatment of painful osteoporotic fractures. Of the materials available, CaP is frequently used as a filling material. Resorption of this material is frequently observed, although clinical outcome is comparable with other cements. Methods: Kyphoplasty utilizing CaP cement was performed in 11 patients with painful osteoporotic vertebral fractures. All patients received a pharmacological antiosteoporosis treatment consisting of calcium, vitamin D, and a standard dose of oral bisphosphonates. Radiomorphologic measurements, pain, and mobility were assessed. Results: Intraosseous and extraosseous CaP cement volumes decreased significantly over 3 years. However, vertebral stability as determined by a constant vertebral body height and the sagittal index was not impaired. Pain improved significantly 2 years after implantation and the mobility scores 1 year after kyphoplasty at least until the third year. Conclusions: Intravertebral CaP cement implants are resorbed slowly over time without jeopardizing stability and clinical outcomes most likely because of a slowly progressing osseous replacement. Extraosseous CaP cement material because of leakages during the kyphoplasty procedure is almost completely resorbed as early as 2 years after the leakage occurred. Therefore, CaP cement is an important alternative to PMMA-based cement materials utilized for kyphoplasty of osteoporotic vertebral fractures.